DEMOKRASI DALAM KAJIAN ISLAM - Dewi Iqlima (Al Hikmah: Jurnal Studi Keislaman, 2016)
In Islamic studies has been known modern terms, modernization, and modernism. For example: "modern streams in Islam" and "Islam and modernization". Modernism in western society implies mind, flow, motion and effort to change the ideology-ideology, customs, old institutions, and so forth, to be adapted to the new atmosphere brought about by advances in science and modern technology. Thoughts and this flow very quickly enter the field of religion, the progress of science and modern technology into the world of Islam, especially after the opening of the nineteenth century, which in the history of Islam is seen as the beginning of the modern period. Further contact with the western world to bring new ideas into the Islamic world, including the idea is democracy. This created problems, which according to Muslim thinkers should be resolved.